PERSPEKTIF TEORI PERILAKU TERENCANA TERHADAP NIAT WAJIB PAJAK ORANG PRIBADI UNTUK MELAKUKAN PELANGGARAN PAJAK - Aprilia Maha Saputri; Endang Kiswara (Diponegoro Journal of Accounting, 2019)
The study aims to analyze the factors that affect the taxpayers intentions to engege in tax foul based on their perception in the perspective of the theory of planned behavior. This study adopt the framework of a previous study conducted by Alleyne and Harris (2017) and add behavior variable. This study using 4 exogenous variable that attitude, subjective norm, perceived behavior control and moral obligation with 2 endogenous variables, namely taxpayers intentions to engege in tax foul and uncomplience tax behavior.The population of this study is the taxpayers that conducting business and/or freelance at KPP Pratama Semarang Candisari. The sampling is carried out by convenience sampling method. The Primary data is collectedby using questionnaire. The number of observation that is collected are 100 questionnaire. The Partial Least Square (PLS) v. 3.2.7 and SPSS v.23.0 are used to test the hypotheses.The finding show that attitude, perceived behavior control, and moral obligation have significant effect to the the taxpayers intentions to engege in tax foul. taxpayers intentions to engege in tax foul have significant effect to uncomplience tax behavior. While the other variable, namely subjective norm does not significant effect to the the taxpayers intentions to engege in tax foul.